CD14 and CD16 expression in noninfectious granulomatous skin diseases - Yuta Ito; Maki Kitakawa; Sachiko Koshikawa; Hideaki Watanabe; Hirohiko Sueki (Frontiers Media S.A., 2020)
Abstract Objectives Peripheral blood monocytes are categorized as classical (CD14++/CD16−) or nonclassical (CD14−/CD16+ and CD14+/CD16+) based on their CD14 expression and CD16 expression. Maturation of classical monocytes produces CD14+/CD16+ macrophages. Our aim was to clarify the in vivo distribution of CD14 and C16 monocytes/macrophages in three granulomatous skin diseases-sarcoidosis, granuloma annulare, and lupus miliaris disseminatus faciei. Methods CD14 and CD16 immunohistochemistry, and CD14/CD16, CD16/CD11c, CD16/CD68, and CD16/factor XIIIa dual labeling were performed in tissues sampled from three cases of sarcoidosis, four cases of granuloma annulare, and three cases of lupus miliaris disseminatus faciei. Results The main infiltrating cell types were CD14+/CD16+ and CD14−/CD16++ macrophages. A small number of CD14+/CD16− macrophages localized along the granuloma periphery. Dual immunofluorescence showed that CD16+ overlapped the most with CD68+ cells, partially overlapped with CD11c+ cells, and did not overlap with FXIIIa+ cells. Conclusions Inflammatory granulomatous skin diseases are characterized by CD16+, mature and inflammatory macrophages; some of which are in the process of maturation.